The growth and yield of common bean (Phaseolus vulgaris L.) as an intercalated crop with coffee (Coffea arabica L.). - Blaco, Moisés (2016)
This article summarizes the results of two trials conducted, in 1991 and 1992, at the Centro Experimental de Café del Pacífico Central-Jardín Botánico, Masatepe, Nicaragua. The main objective was to study the growth and yield behavior of the common bean (Phaseolus vulgaris L.- Rev-81 cultivar) intercropped with coffee (Coffea arabica L.- five years old Catuaí cultivar). A Complete Randomized Block design with two treatments and four replications was used. The treatments were: Bean at First (June to August) and Bean at Last (September to November). Plant height was 43 cm and 47 cm, number of pods per plant was 7 and 4, and weight of 1000 seeds was 21 g and 28 g for the first and second year, respectively. The yield was higher in the first year (710 kg/ha) than in the secondyear (406 kg/ha). In both years there were larger values, for all the assayed variables, in the first cyc1e that in the last cyc1e.